Autoantibodies against ACE2 and angiotensin type-1 receptors increase severity of COVID-19. Issue 122 (August 2021) - Rodriguez-Perez, Ana I.; Labandeira, Carmen M.; Pedrosa, Maria A.; Valenzuela, Rita; Suarez-Quintanilla, Juan A.; Cortes-Ayaso, María; Mayán-Conesa, Placido; Labandeira-Garcia, Jose L.
Abstract: The renin-angiotensin system (RAS) plays a major role in COVID-19. Severity of several inflammation-related diseases has been associated with autoantibodies against RAS, particularly agonistic autoantibodies for angiotensin type-1 receptors (AA-AT1) and autoantibodies against ACE2 (AA-ACE2). Disease severity of COVID-19 patients was defined as mild, moderate or severe following the WHO Clinical Progression Scale and determined at medical discharge. Serum AA-AT1 and AA-ACE2 were measured in COVID-19 patients (n = 119) and non-infected controls (n = 23) using specific solid-phase, sandwich enzyme-linked immunosorbent assays. Serum LIGHT (TNFSF14; tumor necrosis factor ligand superfamily member 14) levels were measured with the corresponding assay kit. At diagnosis, AA-AT1 and AA-ACE2 levels were significantly higher in the COVID-19 group relative to controls, and we observed significant association between disease outcome and serum AA-AT1 and AA-ACE2 levels. Mild disease patients had significantly lower levels of AA-AT1 (p < 0.01) and AA-ACE2 (p < 0.001) than moderate and severe patients. No significant differences were detected between males and females. The increase in autoantibodies was not related to comorbidities potentially affecting COVID-19 severity. There was significant positive correlation between serum levels of AA-AT1 and LIGHT (TNFSF14; rPearson = 0.70, p < 0.001). Both AA-AT1 (by agonistic stimulation of AT1 receptors) and AA-ACE2 (by reducing conversion of Angiotensin II into Angiotensin 1-7) may lead to increase in AT1 receptor activity, enhance proinflammatory responses and severity of COVID-19 outcome. Patients with high levels of autoantibodies require more cautious control after diagnosis. Additionally, the results encourage further studies on the possible protective treatment with AT1 receptor blockers in COVID-19. Graphical abstract: Image 1 Highlights: The renin-angiotensin system (RAS) plays a major role in COVID-19. It is unknown if autoantibodies against RAS components may affect COVID 19 outcome. At diagnosis, AT1 receptor and ACE2 autoantibodies were higher than in controls. At discharge, we found association of autoantibodies and COVID-19 outcome severity. Patients with high RAS autoantibodies require more cautious control after diagnosis.